2010
DOI: 10.1016/j.jallcom.2010.01.105
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical-activated, combustion synthesis of β-SiAlON

Abstract: In this paper, β-Si 6-z Al z O z N 8-z (z = 1) powder was synthesized via combustion synthesis (CS) assisted with mechanical activation by a high energy planetary ball milling under various nitrogen pressures (0.7, 1.0, 1.5, and 2.5 MPa). The effect of ball milling time and nitrogen pressure on the reaction rate and microstructure of CSed products were investigated using XRD and SEM. The effect on the nitrogen pressure required for CS of β-SiAlON was also examined. The results show that prolonged milling time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…β-SiAlON, Si 3 N 4 , and AlN all exhibit excellent thermal performances [1]- [7]. The crystal structure of MgSiN 2 belongs to the orthorhombic system similar to AlN; however, the mechanical properties of MgSiN 2 are superior to those of AlN.…”
Section: Introductionmentioning
confidence: 99%
“…β-SiAlON, Si 3 N 4 , and AlN all exhibit excellent thermal performances [1]- [7]. The crystal structure of MgSiN 2 belongs to the orthorhombic system similar to AlN; however, the mechanical properties of MgSiN 2 are superior to those of AlN.…”
Section: Introductionmentioning
confidence: 99%
“…Most reported syntheses of β-SiAlON via CS required high N 2 pressure (2-150 MPa) to drive the reaction to completion [19]. However, β-SiAlONs have been successfully synthesized under a low nitrogen pressure of 1 MPa as well [20][21][22]. Additionally, inexpensive Si, Al, and SiO 2 powders have been used as raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of ␣-and ␤-SiAlON has been conducted by a variety of processing routes, such as hot isostatic pressing (HIP) [2,4], hot pressing (HP) [10][11][12], gas pressure sintering [7][8][9]13], pressureless sintering [14], liquid-phase sintering [15], carbothermal reduction and nitridation (CRN) [16,17], and combustion synthesis [18][19][20][21][22][23][24][25]. For example, Mandal [4] prepared different ␣-SiAlONs using Si 3 N 4 , AlN, Al 2 O 3 , and Me x O y (where Me = Sr, Ca, La, Ce, Nd, and Yb) by HIP at 1800 • C for 2 h, and observed an elongated morphology in the (Nd + Ca)-and (Ce+Ca)-doped products.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the rapid heating rate and short reaction time of combustion synthesis and the additives like Fe 2 O 3 and NH 4 F were beneficial for the growth of rod-like ␣-SiAlON crystals [18][19][20][21]. By activating the raw materials including Si, Al, and SiO 2 powders in a planetary ball mill for 1-10 h, Yi and Akiyama [22] fabricated ␤-SiAlON powders through SHS in nitrogen of 0.7-2.5 MPa. The ␤ phase of SiAlON with z = 3 and 4 was also produced by combustion synthesis using mechanically activated Si, Al, and Al 2 O 3 powders in nitrogen of 1 MPa [24].…”
Section: Introductionmentioning
confidence: 99%